2015
DOI: 10.1038/onc.2015.139
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12/CXCR4: a symbiotic bridge linking cancer cells and their stromal neighbors in oncogenic communication networks

Abstract: Increasing evidence indicates that the tumor microenvironment has critical roles in all aspects of cancer biology, including growth, angiogenesis, metastasis and progression. Although chemokines and their receptors were originally identified as mediators of inflammatory diseases, it is being increasingly recognized that they serve as critical communication bridges between tumor cells and stromal cells to create a permissive microenvironment for tumor growth and metastasis. Thus, an important therapeutic strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
337
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(347 citation statements)
references
References 170 publications
7
337
1
2
Order By: Relevance
“…bFGF basic fibroblast growth factor, GRO-a melanoma growth stimulating activity a, IL-12Ra interleukin-12 receptor a, IL-12p70 interleukin -12 p70 In this study, we also found that SDF-1 was an independent prognostic factor in addition to the NLR. The interesting scope of the activities of SDF-1 regarding homeostasis of hematopoietic stem and progenitor cells in cancer induced by this chemokine has been highlighted by others [32,33]. SDF-1 (also known as CXCL12) has an important role in maintaining leukocyte homeostasis, especially for myeloid-derived suppressor cells, which includes trafficking and directing the migration of myeloidderived suppressor cells to immune-privileged organs or tumor microenvironments [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…bFGF basic fibroblast growth factor, GRO-a melanoma growth stimulating activity a, IL-12Ra interleukin-12 receptor a, IL-12p70 interleukin -12 p70 In this study, we also found that SDF-1 was an independent prognostic factor in addition to the NLR. The interesting scope of the activities of SDF-1 regarding homeostasis of hematopoietic stem and progenitor cells in cancer induced by this chemokine has been highlighted by others [32,33]. SDF-1 (also known as CXCL12) has an important role in maintaining leukocyte homeostasis, especially for myeloid-derived suppressor cells, which includes trafficking and directing the migration of myeloidderived suppressor cells to immune-privileged organs or tumor microenvironments [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…SDF-1, also known as CXCL12 (chemokine C-X-C motif ligand 12), is a stromal cell-derived factor 1, which is the sole ligand of CXCR4 and a homeostatic chemokine, overexpressed in many human cancers [45,46]. Chemotaxis driven by CXCR4 and SDF-1 interactions has been shown to control various biological functions including cell adhesion, migration, and invasion [47]. Moreover, treatment with AMD3100, a selective CXCR4 antagonist, resulted in increased tumor apoptosis and knockdown of SDF-1, reducing cell proliferation and tumor growth [48].…”
Section: Discussionmentioning
confidence: 99%
“…The role of CXCR4 in numerous physiologic and pathologic circumstances, such as systemic lupus erythematosus, rheumatoid arthritis, and multiple sclerosis, has been elucidated (5). CXCR4 and CXCL12 play decisive roles in tumorigenesis, including the enhancement of cell proliferation, migration, and invasion; cancer cell-tumor microenvironment interactions; and angiogenesis (9)(10)(11).…”
mentioning
confidence: 99%